2019
DOI: 10.3390/antibiotics8040250
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Antifungal Activity of the Licania Rigida Leaf Ethanolic Extract against Biofilms Formed by Candida Sp. Isolates in Acrylic Resin Discs

Abstract: Candida sp. treatment has become a challenge due to the formation of biofilms which favor resistance to conventional antifungals, making the search for new compounds necessary. The objective of this study was to identify the composition of the Licania rigida Benth. leaf ethanolic extract and to verify its antifungal activity against Candida sp. and its biofilms. The composition identification was performed using the ultra-high performance liquid chromatography-quadrupole time-of-flight mass spectrometry (UPLC-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…The analyses of HPLC showed that the species is rich in flavonoids, and such constituents are capable of disrupting fungal membranes [48,49] and may inhibit the budding process and decrease the Ca + and H + homeostasis [50]. In the present study, caffeic acid and quercetin were the major compounds present in both extracts of M. suaveolens with caffeic acid standing out, as it is always present in the chemical composition of M. suaveolens extracts [22,51].…”
Section: Discussionsupporting
confidence: 50%
“…The analyses of HPLC showed that the species is rich in flavonoids, and such constituents are capable of disrupting fungal membranes [48,49] and may inhibit the budding process and decrease the Ca + and H + homeostasis [50]. In the present study, caffeic acid and quercetin were the major compounds present in both extracts of M. suaveolens with caffeic acid standing out, as it is always present in the chemical composition of M. suaveolens extracts [22,51].…”
Section: Discussionsupporting
confidence: 50%
“…an example is the Felix instruments leaf spectrometer, used with a quality meter. 111 The Ci-710 Miniature leaf spectrometer was used to detect the leaf quality and the effects of pests, drought, and pathogens. 112 The quality meter can detect the acidity, colour, and total soluble solids of fruit.…”
Section: Application Of Fertilizermentioning
confidence: 99%
“…The flavan-3-ols Epiafzelechin (compound 38), Catechin (compound 39), (epi)Catechin (compound 40), and Gallocatechin (compound 41) have been characterized as components of millet grains [23], G. linguiforme [25], Camellia kucha [38], strawberry, cherimoya [39], Rosa rugosa [40], Myrtle [41], Radix polygoni multiflori [42], Licania ridigna [43], and Rhodiola rosea [44]. The flavan-3-ol Gallocatechin (compound 41) was found in extract of R. rugosa and R. davurica.…”
Section: Flavan-3-olsmentioning
confidence: 99%
“…The fragment ion with m/z 245 yielded four daughter ions at m/z 243, m/z 217, m/z 173, and m/z 145. It was identified in the bibliography in extracts from G. linguiforme [25], Licania ridigna [43], and Rhodiola rosea [44].…”
Section: Flavan-3-olsmentioning
confidence: 99%
See 1 more Smart Citation